Controlling the blood flow in the stenosed porous artery with magnetic field - D.F. Jamil,; R. Roslan,; M. Abdulhameed,; I. Hashim, (Penerbit Universiti Kebangsaan Malaysia, 2018)
The unsteady blood flow in the stenosed porous artery subjected to a magnetic field was studied analytically. Oscillating pressure gradient and periodic body acceleration were imposed on the flow field. The effects of the magnetic field and the permeability of the stenosed artery on the blood velocity were studied. The results showed that the magnetic field affected the flow field significantly which can be beneficial for some practical problems.